Hudibras : in three parts / written in the time of the late wars by Samuel Butler ... ; with large annotations and a preface by Zachary Grey ; in two volumes. - Butler, Samuel, 1612-1680. (Tufts University. Tisch Library., 2015)
Volume 2 of 2.; 1 online resource (2 volumes) : illustrations, plates (1 folded), portrait.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.